Empowering Women Through Physical Education: Developing Inclusive Policies for Gender Equality in Sports Participation - Rathee, Sumit; Rathee, Anil; Yadav, Sanjeev Kumar (Journal of Neonatal Surgery, 2025)
When it comes to physical education, where long-established gender stereotypes still play a role, gender inequality is an especially big problem. The importance of creating inclusive policies that promote physical education as a means to empower women by guaranteeing equal chances for involvement, advancement, and leadership in sports. the societal norms, institutional prejudices, and resource constraints that women experience in sports, as well as the effect of gendered views on women's participation in physical activities. ways in which gender-inclusive legislation, changes to curricula, and focused professional development for educators can foster inclusive settings that promote equal participation of girls and women in physical education. Provide schools, teachers, and lawmakers with actionable advice based on an analysis of case studies and effective programs to advance gender parity in athletics. In the end, it all comes down to how promoting physical education for women may lead to larger social shifts, creating a more accepting culture where people of all genders can participate in sports without discrimination.